Book of Hours Geofroy Tory, Spirit Renaisans dalam Kontinuitas Ide Desain - Fitro Nur Hakim - STMIK Provisi Semarang (SPEED - Sentra Penelitian Engineering dan Edukasi, 2017)
Abstract: Graphic design work is widely known in commercial products, such as print ads, televisionand internet. Beginning with the application of engineering design and technology actually beganduring the Renaissance. Media distribution of graphic design has undergone a major evolution.Analysis of the work "Book of Hours" by Troy Geofroy will reopen the human insight appreciation ofworks of graphic design. Renaissance is a graphic design revival in the year 1500, the designersstretched penetrate into the realm of mass media. A design activity is contrary to custom in the past,offered a more graphic designs for religious work.Without prejudice to the religious spirit in his design work, Geofroy Troy has mediated a designidea that is more useful for many people. Book of Hours work Geofroy Troy has given occasion tomany human beings, to share in the design work of a "prayer book" which previously was theexclusive object belongs to rich people. Printing machines and techniques of human geometry hasmade it easier to facilitate human needs for graphic design products in his life.Keywords : Renaissance graphic designAbstrak: Karya desain grafis banyak dikenal dalam produk-produk komersil, misalnya iklan cetak,televisi dan internet. Awal mula desain dengan penerapan teknik dan teknologi sebenarnya dimulaipada masa Renaisans. Media sebaran desain grafis telah mengalami evolusi besar. Analisis terhadapkarya "Book of Hours" oleh Geofroy Troy akan membuka kembali wawasan manusia akanapresiasinya terhadap karya-karya desain grafis.Renaisans merupakan sebuah kebangkitan desain grafis ditahun 1500, para desainermenggeliat merasuk ke ranah media massal. Sebuah aktivitas desain yang bertolak belakang dengankebiasaan pada masa sebelumnya, yang lebih mempersembahkan desain grafis untuk pekerjaanreligius. Tanpa mengurangi spirit religi dalam karya desainnya, Geofroy Troy telah memediasi sebuahgagasan desain yang lebih berguna bagi masyarakat banyak. Book of Hours karya Geofroy Troy telahmemberi kesempatan kepada banyak insan, untuk ikut menikmati sebuah karya desain berupa "bukudoa" yang sebelumnya merupakan benda eksklusif milik orang-orang kaya. Mesin cetak dan teknikilmu ukur telah memudahkan manusia untuk memfasilitasi kebutuhan manusia terhadap produkdesain grafis dalam hidupnya.Kata kunci : Desain grafis Renaisans